Euphorbia motuogensis (Euphorbiaceae), a new species from Xizang, China - Li, Man-Ting; Lan, Xiao-Zhong; Zuo, You-Wei; Deng, Hong-Ping (Phytotaxa, 2021)
Euphorbia motuogensis M. T. Li, X. Z. Lan, H. P. Deng & W. L. Zheng, sp. nov., a new species from Motuo, Tibet, China, is described and illustrated here. It is closely similar to Euphorbia sikkimensis in having terete root, alternate leaves, well-developed pseudoumbellate inflorescence, cyathium, smooth and glaborus capsule, but Euphorbia motuogensis is clealy distinguishable by its pilose stems, involucral leaves color, secondary involucral leaves absent, cyathophylls number and color, and five similar glands. Furthermore, molecular phylogenetic analyses of sequences from both nuclear ribosomal ITS confirm that this species is distinct from morphologically similar species in this subgenus.